Design Electric Bells to Improve Kinesthetic Intelligence for the View Image in the Library and Archive Department of Bengkulu Province - Haris Farhan; Fransiska Timoria Samosir; Aang Gunaidi (UNIB Press, 2023)
This study aims to design an electric bell and determine the kinesthetic improvement ability of visually impaired people after using the Dewey Decimal Classification (DDC) listicv bell as an information guide. When a visitor wants to know the braille book, title, location, and classification of Dewey (DDC) then it is necessary to press the DDC bell and it will ring. People with visually impaired disabilities were the subjects of this study, and ten people as the object. Data collection using Tests, interviews, and documentation is used to collect data. The method used quantitative experiments. In addition, descriptive analysis showed that the average pre-test score was 25.87 and the average post-test score was 21.05. so Ha is accepted and Ho is rejected. The results of the study stated that the use of the Dewey electric bell (DDC) by the Bengkulu Provincial Library and Archives Service affected the kinesthetic ability of movement, visual and motor recognition of book classifications for the visually impaired.